2008
DOI: 10.1016/j.physletb.2008.07.090
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of parton distributions of strange quarks in the nucleon from charged-kaon production in deep-inelastic scattering on the deuteron

Abstract: The momentum and helicity density distributions of the strange quark sea in the nucleon are obtained in leading order from charged-kaon production in deep-inelastic scattering on the deuteron. The distributions are extracted from spin-averaged K� multiplicities, and from K� and inclusive double-spin asymmetries for scattering of polarized positrons by a polarized deuterium target. The shape of the momentum distribution is softer than that of the average of the and quarks. In the region of measurement 0.02 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
142
5
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(166 citation statements)
references
References 36 publications
18
142
5
1
Order By: Relevance
“…Combined analysis of parity violating ep asymmetries and ν p elastic data, used for the extraction of the strange axial form factor, also suggests a negative strange quark contribution [13]. Surprisingly, these results are at variance with the most recent determinations of the strange quark distribution ∆s(x) from SIDIS, which appears to be compatible with zero [14] or even slightly positive [15], at least in the x range of the measurements. Among possible explanations for this observation, a substantial breaking of the SU(3) f symmetry has been advocated [16].…”
Section: Introductionmentioning
confidence: 76%
“…Combined analysis of parity violating ep asymmetries and ν p elastic data, used for the extraction of the strange axial form factor, also suggests a negative strange quark contribution [13]. Surprisingly, these results are at variance with the most recent determinations of the strange quark distribution ∆s(x) from SIDIS, which appears to be compatible with zero [14] or even slightly positive [15], at least in the x range of the measurements. Among possible explanations for this observation, a substantial breaking of the SU(3) f symmetry has been advocated [16].…”
Section: Introductionmentioning
confidence: 76%
“…1(a). For the isoscalar deuteron nucleus, the kaon multiplicity is expressed in leading order as follows [14,23]:…”
Section: Extraction Of S(x) From Hermes Kaon Sidis Datamentioning
confidence: 99%
“…Since the probability for the |uudQQ Fock state is expected to be roughly proportional to 1/m 2 Q , where m Q is the mass of quark Q, these light-quark intrinsic seas should be more abundant than the intrinsic charm quark. Using the kaon SIDIS data from HERMES on s(x) +s(x) [14], the E866 Drell-Yan data ond(x) −ū(x) [16], and the CTEQ6.6 PDF [21], it was shown that the probabilities for the |uuduū , |uuddd , and |uudss Fock states have been extracted, supporting the existence of the intrinsic light-quark sea [20].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Those data provide additional constraints on the s-quark PDF in a much wider kinematical range for Q 2 . The HERMES data on semi-inclusive DIS kaon production [9] can also potentially constrain the strange sea, however the strange sea extracted from those data still suffer from substantial uncertainty due to the modeling of low-Q 2 kaon production [10] therefore they are not included into our analysis.…”
Section: Introductionmentioning
confidence: 99%